2005
DOI: 10.1007/s11244-005-3788-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous photocatalysis: state of the art and present applications In honor of Pr. R.L. Burwell Jr. (1912–2003), Former Head of Ipatieff Laboratories, Northwestern University, Evanston (Ill).

Abstract: In the present paper, the basic fundamentals of photocatalysis are explained with the influence of the five main parameters which govern the kinetics: (i) mass of catalyst, (ii) wavelength, (iii) partial pression and/or concentrations of reactants, (iv) temperature (at a second degree) and (v) the radiant flux. The main types of photocatalytic reactions presently described (all performed at room temperature) concern (i) the selective mild oxidation of hydrocarbons, (ii) the hydrogen production and (iii) the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
243
0
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(273 citation statements)
references
References 74 publications
10
243
0
20
Order By: Relevance
“…[19][20][21][22] In this study, a reasonable agreement (R 2 = 0.9687) was obtained between the experimental results and the linear form of the L-H expression (equation 1). This expression used values of 1.46 × 10 -5 mol L -1 min -1 and 2.92 × 10 3 mol -1 L for the reaction kinetic constant (k) and the adsorption constant (K), respectively.…”
Section: Effect Of Initial Styrene Concentrationsupporting
confidence: 78%
“…[19][20][21][22] In this study, a reasonable agreement (R 2 = 0.9687) was obtained between the experimental results and the linear form of the L-H expression (equation 1). This expression used values of 1.46 × 10 -5 mol L -1 min -1 and 2.92 × 10 3 mol -1 L for the reaction kinetic constant (k) and the adsorption constant (K), respectively.…”
Section: Effect Of Initial Styrene Concentrationsupporting
confidence: 78%
“…7 While the apparent activation energy determined in our work is based on the formation rate constant of adsorbed cyclohexanone, previous studies only evaluated the formation rate of desorbed cyclohexanone. 7,8 This may explain the difference in apparent activation energies found, since the latter is influenced by sorption effects. The in situ ATR-FTIR technique appeared very suitable for distinguishing these effects.…”
Section: Discussionmentioning
confidence: 95%
“…6 Few studies have analyzed the effect of elevated temperature on the behavior of the photocatalyst, which might be a means to stimulate cyclohexanone desorption, and thus prevent extensive over-oxidation to carboxylates and the accompanying deactivation. Herrmann et al 7,8 concluded that the reaction was not limited by adsorption or desorption steps in the temperature interval of 23-55 1C, where the activation energy was estimated at 10.5 kJ mol À1 . Product desorption and reactant adsorption were proposed to be limiting reaction rates at lower (o23 1C) and higher temperatures (>55 1C), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, solar photoabatement of pollutants uses the sun as energy source and works at atmospheric conditions degrading pollutants present in low atmospheric concentrations. Photocatalysis is able to oxidize a wide spectrum of contaminants, not requiring any additional chemicals and using a relative low-cost material [6,8,9]. During a photocatalytic process, the semiconductor exposed to sunlight radiation absorbs photons with energy higher than its band gap and injects electrons from the valence to the conduction band, creating electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%